2020
DOI: 10.24123/jmb.v19i2.466
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Financial Ratios for Predicting Bankruptcy in SMEs Listed on PEFINDO25

Abstract: This study aims to analyze the Financial Ratio for Predicting Bankruptcy. The sample used in this study are SMEs according PEFINDO25 period 2013 to 2017. The independent variables in this study is liquidity, profitability, debt structure, solvency and activity ratio; and control variables is size and age, as well as the dependent variable is bankruptcy. The amount of sample in this study 32 companies PEFINDO25 by using purposive sampling. The method of data analysis is done by using logistic regression with SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Pagaddut (2021) researched on Philippine micro, small and medium enterprises to determine the influence on financial performance and those financial ratios-specifically, the debt ratio, asset turnover, and gross profit margin-have a major impact on that performance. Other similar studies done by Rettobjaan (2020) showed that bankruptcy is significantly impacted negatively by liquidity, profitability, and age. The debt arrangement significantly reduces the likelihood of bankruptcy.…”
Section: Literature Reviewmentioning
confidence: 74%
“…Pagaddut (2021) researched on Philippine micro, small and medium enterprises to determine the influence on financial performance and those financial ratios-specifically, the debt ratio, asset turnover, and gross profit margin-have a major impact on that performance. Other similar studies done by Rettobjaan (2020) showed that bankruptcy is significantly impacted negatively by liquidity, profitability, and age. The debt arrangement significantly reduces the likelihood of bankruptcy.…”
Section: Literature Reviewmentioning
confidence: 74%
“…In theory, an increase in profitability should reduce the likelihood of financial distress and failure (Chiaramonte & Casu, 2017). Rettobjaan (2020), This study aims to a study that aimed to analyze the Financial Ratio for Predicting Bankruptcy. The sample used in this study were SMEs according to PEFINDO25 period 2013 to 2017.…”
Section: Bankruptcy Risk Indicatorsmentioning
confidence: 99%